FORMULATION OF POLYHERBOMINERAL MATRICES FOR TREATMENT OF OSTEOPOROSIS - Mulchand, Shende; Seema, Mendhekar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Herbal drugs are finding the new source of promising drugs for the treatment and cure of various ailments. The present research work deals with the formulation and evaluation of herbomineral formulation indicated for osteoporosis. Materials and Methods: The aqueous extract of Terminalia arjuna (ARJ), Asthisamhara (ASTM), Gokhru (GKH), Ashwagandha (ASG) and dried powder of drugs Sunthi (ST), Padmakashta (PDMS), Laksha (PLSH) and Jestamadha were prepared and formulated into a herbomineral tablet with organic calcium viz.; Godanti Bhasma (Godan) and Kukkutandatvak Bhasma (Kukk) by wet granulation. Results: The prepared tablets were evaluated for various parameters such as colour, average weight, hardness, friability and disintegration time, which were found acceptable as per pharmacopoeial specifications. The weight variation (450 mg±10%), pH (4.58), disintegration time (17 min) and hardness (1.25 kg/cm2) were found within acceptable range. The quantitative estimation of calcium by atomic absorbance spectrophotometry was carried out using ethanol-water solvent extraction method and found 76.27 ± 0.439 mg/tab of elemental calcium in optimized F4 formulation. Conclusion: The developed herbomineral formulation is suitable for calcium deficiency by balancing hormonal imbalance and increases the rate of ossification of bone which helps to curing bone fracture, osteoporosis and calcium deficiency related problems.